The moderating effect of board independence on the relationship between sustainability reporting and firm performance - Jocelyn Mok Pau Chee; Mohd Ashari Bakri (Universiti Malaysia Sabah, 2023)
The purpose of this study is to investigate the moderating effect of board independence on the relationship between sustainability reporting and corporate performance. The study examined a total number of top 200 firm in Malaysia (based on market capitalization) from the period of 2012 to 2021. The data for the study was obtained from DataStream and the annual report was extracted from Bursa Malaysia's website. To examine the data, the study used panel data analysis, specifically pooled OLS, random and fixed analysis were used. We also use robust standard error estimation as a robust analysis to mitigate the potential problems of serial correlation and heteroskedasticity. The study reveals that board independence play significant role in moderating the relationship between sustainability reporting and firm performance. The results indicate that board independence enhances corporate transparency in a way it promotes firm participation in sustainability reporting and as a results investor that value sustainability reporting stand and proposition would place better firm valuation. The results of the study shed light on how crucial board independence in enhancing the sustainability reporting and firm performance relationship. Additionally, it also helps managers tailor their investment strategies to the needs of their clients, especially to those investors that concern on sustainability reporting.